Sudanese library anxiety constructs - Abusin, K.A.; Zainab, Awang Ngah; Karim, N.H.A. (SAGE Publications, 2011)
Library anxiety is manifested in the form of negative feelings, fear, stress, distress, confusion and has debilitating effects on students' academic performance, which makes it a serious phenomenon for investigation. This study explores library anxiety amongst Sudanese university students and identifies factors that contribute to this phenomenon. The factors were identified using the diary approach collected from 51 third year undergraduate students who were taking the research method course at the Sudan University of Science and Technology for the first time. The analysis of diary entries revealed eight library constructs named Sudanese Library Anxiety Construct (SULAC). The constructs comprises Negative perceptions towards academic library environment, Negative perceptions towards library staff, Affective barriers, Negative perceptions towards peers, Negative perceptions towards library services, Negative perceptions towards library collections, Negative perceptions towards library regulations, and Cognitive barriers. Details of factors underlying each construct are described.